Design Of Automated Payment System Using Rfid Technology - Hasnni, Nur Zakiah Shahrul (Universiti Sains Malaysia, 2017)
RFID which is also known as Radio Frequency Identification is a kind of identification device which uses radio frequency to operate. The RFID application that is widely used is an automated payment system. An efficient payment system is needed to ease the user during shopping. The main purpose of this project is to design an automated payment system using RFID technology which can help to shorten the queue during payment hence make the payment activity become more effective. The main hardware needed for this system are RFID reader, RFID tag, and RFID antenna. Every tags with their own ID number will be attached to every items. The RFID reader will work by reading the data on the tag during payment activity. Serial communication is used as a communication between RFID reader and PC. RFID reader will be set according to the requirements so that it will be able to read the tag. A graphical user interface is used to show the detail of the cost. The user also able to make choice if they want to cancel any item after scanned or continue with payment process. The time taken during payment system using RFID technology is able to be saved by 63.12% compared to normal system currently used which is barcode scanner system.